2016
DOI: 10.1007/s10854-016-5157-2
|View full text |Cite
|
Sign up to set email alerts
|

Compositional variation of structural, electrical and magnetic properties of Dy substituted Ni–Co spinel ferrite

Abstract: In the present work nanocrystalline dysprosium substituted Ni 0.8 Co 0.2 Fe 2-x Dy x O 4 (x = 0.00, 0.025, 0.050, 0.075 & 0.1) ferrite system was synthesized by the solution combustion method. The phase formation has been confirmed by Reitveld analysis of XRD patterns, which is a characteristic of spinel ferrite with most intense (311) peak. The bond lengths and site radii of tetrahedral and octahedral sites are found to increase with increase in Dy content. IR measurements showed two prominent bands which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…According to the literature review, Y 3+ magnetic moment is 0 μ B . Kadam and Rajpure reported that the nickel‐cobalt ferrites, the ratio of iron ions in A site and B site is about 1:1. So before the doping, the theoretical value is about 2.4 μ B .…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature review, Y 3+ magnetic moment is 0 μ B . Kadam and Rajpure reported that the nickel‐cobalt ferrites, the ratio of iron ions in A site and B site is about 1:1. So before the doping, the theoretical value is about 2.4 μ B .…”
Section: Resultsmentioning
confidence: 99%